Effect of Ion-Exchange Modification on Hydrogen and Carbon Dioxide Adsorption Behaviour of RhoZMOF Material - Guillermo Calleja; Juan A. Botas; Carmen Martos; Gisela Orcajo; José. A. Villajos (Adsorption Science & Technology)
Zeolite-like metal-organic frameworks (ZMOFs) can adsorb hydrogen and carbon dioxide because of their negatively charged structures, being able to be ion exchanged with metal cations to further increase the electrostatic field inside the framework cavities. Ion exchange of RhoZMOF with alkaline and alkaline-earth metal cations was performed up to stoichiometric levels with one single ion-exchange step. Screen effect caused by water-coordinated molecules around the exchanged cations hindered the hydrogen uptake, although slightly higher heats of hydrogen adsorption were observed for Na + , Li + , Mg 2+ and Ca 2+ exchanged samples. Conversely, the same exchange treatment produced a very interesting enhancement in CO 2 adsorption of RhoZMOF at 303 K. Moreover, because there are no water molecules surrounding the metallic cations, RhoZMOF material was exchanged with an Li + –crown–ether complex in the nitrobenzene/acetonitrile mixture, free of water. Nitrogen and hydrogen adsorption isotherms at 77 K showed higher specific surface area and hydrogen adsorption capacity than the material with hydrated cations.